Kpando, Volta Region, Ghana. Archaeology and ›Shared Heritage‹ of German Colonialism in Former Togoland. Research in 2022 and 2023 - Kleinitz, Cornelia; Apoh, Wazi; Fiador, Ernest K.; Kurapkat, Dietmar; Linstädter, Jörg; Loges, Kathrin; Verstegen, Ute; Zeitler, Annika (e-Forschungsberichte des DAI, 2023)
A cooperative project focusing on the archaeology and ›shared heritage‹ of German colonialism in the former Togoland colony brings together capacities from Ghanaian and German partners in the fields of archaeology, history, ethnography, architecture/building archaeology and surveying/cartography. The project aims to document, research, preserve, and present built heritage from the German colonial period in close consultation and cooperation with local authorities and communities. Building on extensive archaeological research on German missionisation and colonisation of Togoland led by Wazi Apoh and students over the past 20 years, the project partners initially focus on archival and building archaeological research, including damage assessments and restoration/rehabilitation planning in addition to (GIS-)mapping. This report outlines preliminary results from preparatory research in 2022 and a first field season in the Volta Region of Ghana in early 2023, and it highlights possible avenues for further work.